The effect of haze among employee at the Department of Environment (DOE) / Nur Fazlyana Mohd Amir and Siti Nor Hafiza Abdullah - Mohd Amir, Nur Fazlyana; Abdullah, Siti Nor Hafiza (Faculty of Business and Management, 2016)
In Malaysia today, the effect of haze becomes a widespread issue faced by employee in many organizations. In a year, regularly we had been encountered the situation of haze affecting our daily tasks and routines. This problem will give the bad impact towards the health and other factors of individuals or the country itself. In other words, we can see the effect of haze towards employee in the organizations. During haze period, it causes the barriers and reduces the employee capability to perform their tasks especially who are working on outdoor. Being aware of this issue, the research study focused on two dimensions that influence productivity among employee at the Department of Environment (DOE) which are haze impact on physical and psychological health. The respondents consist of 82 persons of male and 83 persons of the female. Data is collected through questionnaires distributed to 165 employees in the Department of Environment (DOE) using non-probability sampling. The result of the present study showed that the significant correlation relationship between factors that influence productivity. This study also used regression backward analysis in order to identify the relationship between factors and productivity among employees at the Department of Environment (DOE). This study is said to be beneficial to the company in Malaysia, especially if they are facing the low productivity among employees. It will help them to gain awareness on the main factor and help them to manage the issue from getting worse. Recommendations for future research and company are also being discussed.